Residents’ Perception Of Liveable Neighbourhood Environment In Subang Jaya, Selangor, Malaysia - Lau, Jasmine (2008)

(untitled)
The complex interaction between the community and its environment could be exemplified through the term liveability. A liveable neighbourhood is one that offers quality and good environment to ensure inhabitants are able to live their lives in a satisfying way. In relation to these, the three-fold objectives have been formulated for this study. They are (1) to assess the importance residents accorded to various dimensions and attributes in determining neighbourhood liveability, (2) to discover residents’ satisfaction level toward the liveability dimensions and (3) to explore the importance of the socio-demographic variable in predicting satisfaction with neighbourhood and liveability dimensions. Reviewing the literature found that four dimensions (social, physical, functional and safety) are commonly used to understand liveability issues in the living environment. Sixteen attributes are also identified to be relevant and are utilised as an indicator for each of the four dimensions. Data was collected using mailed questionnaires and from 300 questionnaires mailed, 170 were returned making the response rate of 57%. Analysis indicated that residents are more concerned about the safety dimension while social dimension is deemed to be the least important dimension. An overall ranking for all attributes shown that three safety attributes topped the list. The bottom of the list sees the attributes from social and functional dimensions. Satisfaction rankings were done using the mean value and Yeh’s index. Both methods revealed that residents attributed the highest satisfaction toward their functional environment. However, the mean value indicated that residents are most dissatisfied with the social environment while Yeh’s index shown that residents were least satisfied with the safety level. In assessing the importance of socio-demographic characteristics as predictor variables, the variance obtained ranged from 10% to 20%. This means that regression models modestly fit the data and future research should consider including other variables. The length of residency is a significant predictor of satisfaction in four models except for safety dimension. In addition, Indian ethnicity predicted variance in satisfaction for neighbourhood, physical environment and social environment. Among all the models, none of the demographics variables are reliable in predicting satisfaction with the safety level.